Pengaruh Fraud Diamond terhadap Potensi Kecurangan Laporan Keuangan Perusahaan Sektor Barang Baku yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Wiguna, Natasya; Prasetyo, Ari Hadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Financial reports include the company's financial performance and other information used to make decisions. So companies compete to produce good financial reports and even allow management to manipulate financial reports to make them look good. Therefore, this research aims to examine the effect of fraud diamonds on financial statement fraud. Fraud diamond consists of Pressure which consists of financial stability, external pressure, and financial targets, Opportunity which consists of ineffective monitoring and nature of industry, Rationalization, and Capability. The population of this research is raw goods sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. 99 sample data were obtained during 3 years of observation with the sampling technique used was the purposive judgment sampling method. The analytical method used is logistic regression analysis using the SPSS version 26 program. The conclusion of this research shows that the variables ineffective monitoring, change in auditor, and change of director have a significant positive effect on the tendency of financial statement fraud. Meanwhile, the variables financial stability, external pressure, financial targets, nature of industry do not have a significant effect on the tendency for financial statement fraud.